Trinidad and Tobago Basic Sector Study Survey - Wood, John (International Book Development, 1994)
This study involved the design of a practical survey instrument and procedure to find out about textbooks, supplementary reading, and other learning resources in primary schools in Trinidad and Tobago. The report makes recommendations for the conduct of the survey. A copy of the survey instrument is appended.
Keywords: textbooks; supplementary reading